2014
DOI: 10.2527/jas.2014-8055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elevated ambient temperature at parturition on duration of gestation, ruminal temperature, and endocrine function of fall-calving beef cows1

Abstract: Fall-calving Angus cows were used to evaluate the effect of ambient temperature on duration of gestation. In Exp. 1, cows were AI and calved in August (n = 14) or October (n = 10). Cows grazed native prairie pasture in Oklahoma and had a BCS of 6.0 ± 0.5 (1 = emaciated, and 9 = obese) at parturition. Commencing 2 wk before the expected calving date, blood samples were taken from the coccygeal vein every 2 to 3 d until calving. Cows that calved in August tended to have shorter gestations (P = 0.07) compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Nevertheless, our findings were numerically comparable with the studies of Mikláš et al (2019b) who in one dairy herd observed longest gestation lengths in winter and partialy also with the work of Tomasek et al (2017). Some authors explain thesse changes by variable temperatures at calvings, with shortest gestation lengts in summer (Wright et al, 2014). However, we did not confirm this suggestion.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Nevertheless, our findings were numerically comparable with the studies of Mikláš et al (2019b) who in one dairy herd observed longest gestation lengths in winter and partialy also with the work of Tomasek et al (2017). Some authors explain thesse changes by variable temperatures at calvings, with shortest gestation lengts in summer (Wright et al, 2014). However, we did not confirm this suggestion.…”
Section: Resultssupporting
confidence: 73%
“…In terms of gestation length, Wright et al (2014) reported shortening of gestation length due to higher temperatures. Moreover, shorter gestation length may reduce the time of foetal growth, resulting in worsened performance of dams'…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress has been linked to fewer mounts per cycle in the summer and a longer interval between mounts [ 149 ]. Cortisol levels increase more prior to calving in August than prior to calving in October and gestation is shorter in summer than in winter [ 150 ].…”
Section: Main Stressors In the Beef Cowmentioning
confidence: 99%
“…However, heat stress can negatively affect reproductive function of beef cows. For example, cows exposed to elevated ambient temperature during late gestation experienced premature onset of parturition due to increased body temperature (Wright et al, 2014). In feedlots, animals experience radiant heat from dirt or concrete surfaces and without appropriate management will show performance loss due to decreased efficiency and feed intake resulting from physiological stress (Mader et al, 2006).…”
Section: Management Optionsmentioning
confidence: 99%